Reasons for Tooth Removal in Adults: A Systematic Review - Dyonne L.M. Broers; Leander Dubois; Jan de Lange; Naichuan Su; Ad de Jongh (Elsevier, 2022)
Objective: Most tooth extractions are performed for dental reasons, but there are also nondental and nonmedical reasons for extractions; these include psychological, financial, religious, and cultural reasons as well as simply granting a patient's request. This systematic review was performed to examine the proportion and range of indications associated with tooth removal in context of dental, nondental, and medical reasons. Methods: A search conducted using PubMed, Embase, and APA PsycINFO identified 6038 studies. Three studies (4396 extractions in total) could be included for the risk of bias assessment and qualitative data synthesis. Results: The reported indications for tooth extraction on dental and medical grounds included caries with the proportion of all extractions ranging from 36.0% to 55.3%, periodontitis from 24.8% to 38.1%, trauma from 0.8% to 4.4%, periapical disease from 7.3% to 19.1%, orthodontics from 2.5% to 7.2%, and other reasons from 4.5% to 9.2%. The proportion for patient requests ranged from 3.6% to 5.9%, but specific information regarding the actual reasons for extraction could not be determined. Conclusion: The results suggest that caries and periodontitis are the most common indications for tooth extraction and that studies to reliably estimate the incidence of nondental and nonmedical motivation for extraction are lacking. Given that the final decision on performing or refusing extractions, whether it be based on dental, nondental, or nonmedical reasons, largely rests with the dentist and oral surgeon, detailed guidelines are warranted.